Investigation on Antioxidant Compounds from Marine Algae Extracts Collected from Binuangeun Coast, Banten, Indonesia - Muhammad Nursid; Endar Marasskuranto; Karren Budi Atmojo; Mulyo Pandu Hartono; Maria Diyah Nur Meinita; Riyanti R (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2016)
Marine algae contains bioactive secondary metabolites that have potential to be developed as antioxidant. The aims of this research were to investigate antioxidant activity and total phenolic compound of marine algae collected from Binuangeun Beach, Banten and to characterize antioxidant compounds from selected algae species. Antioxidant activity was determined by 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) assay and Ferric Ion Reducing Antioxidant Power (FRAP) Assay, while total phenolic content was estimated by Folin-Ciocalteau method. Isolation of bioactive antioxidant compound was performed using SiO2 column chromatography and preparative high performance liquid chromatography (HPLC). The antioxidan activity evaluation was conducted to methanol extracts from 20 species (7 Chlorophyta, 9 Phaeophyta and 4 Rhodophyta). Results showed that Padina australis extract was found to be the most active. The major bioactive antioxidant compound was identified as fucoxanthin and a polar compound that was suspected as phenolic compound. The extracts of P. australis presented the highest phenolic content (58.59 mg GAE/g). A significant correlation between antioxidant capacity and total phenolic content was found, indicating that phenolic compounds are the major contributors to the antioxidant properties of P. australis.